Donor-site safety in microvascular lymph node transfer for breast cancer-related lymphedema using reverse lymphatic mapping—A prospective study - Pajula, Susanna; Saarikko, Anne; Suominen, Sinikka; Kaartinen, Ilkka; Kiiski, Juha; Mani, Maria; Halle, Martin; Hartiala, Pauliina (Elsevier, 2025)
Background: Vascularized lymph node transfer (VLNT) is one option among other surgical treatments in the management of breast cancer-related lymphedema (BCRL). The cause of concern regarding VLNT harvested from the groin has been the potential development of secondary lower-extremity lymphedema. This study explored the risks associated with donor-site morbidity following groin VLNT, with or without concomitant breast reconstruction.
Method: The cohort comprised data from the Lymfactin® Phase I and II trials, conducted from 2016 to 2019, that used perioperative reverse lymphatic mapping. The volume of the lower extremities was measured preoperatively and at 3, 6, and 12 months postoperative, and the adverse events were documented during study visits.
Results: Altogether, 51 women with a mean age of 55.5 years were recruited. The mean duration of BCRL was 31.8 months. Among these, 25 (49%) underwent VLNT (VLNT-group) and 26 (51%) underwent VLNT in combination with breast reconstruction (VLNT-BR group). The groups were similar in terms of age, (p = 0.766), BMI (p = 0.316), and duration of BCRL (p = 0.994). Across a period of one year, the volume difference between the lower extremities changed by 22.6 ml (range: -813 to 860.2 ml) (p = 0.067). None of the patients had lower-extremity volume difference exceeding 10% at the 12-month follow-up visit. The most frequent adverse events were postoperative pain (17.7%), wound healing issues (11.8%), and seroma formation (11.8%). Most adverse events (64.6%) were classified as minor.
Conclusions: This prospective study demonstrated that groin VLNT with reverse lymphatic mapping appears safe and does not increase the risk of secondary donor-site lymphedema within one year postoperatively.